Ukrainian Antarctic Research: current Bibliography (2012 - 2015) - Videnina, N. G.; Rybachuk, V. P.; Fedchuk, A. P.; Prymachenko, S. I. (Ukrainian Antarctic Journal, 2016)
The bibliographic descriptions of the Ukrainian scientific works on Antarctica that were published domestically and abroad in 2012-2015 are listed herein. This bibliographic data extends and complements the 2010-2011 current bibliography of national publications, presented in the “Ukrainian Antarctic Journal” in 2012 (issue 10-11). The abstracts were collected from Ukrainian scientific journals, collections, and conference proceedings as well as national (“Dzherelo”, “Litopys zhumal’nykh statej”, etc.) and international (“Antarctic Bibliography”, “Scopus”, “Google scholar”, “Scirus”, “e-Library”, etc.) bibliographic databases. In total 214 publications were compiled on the topics of Antarctic research within the last four years.